2009
DOI: 10.1002/app.30611
|View full text |Cite
|
Sign up to set email alerts
|

Preparation, characterization, and surface energetics of hydroxypropyl cellulose/polyethylenimine blends

Abstract: Blend films composed of hydroxypropyl cellulose (HPC) and polyethyleneimine (PEI) were prepared by solution casting method. The structure and mechanical properties of the blend films were analyzed by attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopy and tensile strength tests. The ATR-FTIR results indicated that there is a 5 cm À1 band shift to higher wave number due to the formation of hydrogen bonding between HPC and PEI components. The mechanical properties of the blends, such … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Circular films, 10 mm in diameter and 100 mm thick, were introduced in the disks. The plates were incubated at 37 C for 24 h. Diameter of the inhibition zone depends both on the polymer present in the disk and on microorganism susceptibility.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Circular films, 10 mm in diameter and 100 mm thick, were introduced in the disks. The plates were incubated at 37 C for 24 h. Diameter of the inhibition zone depends both on the polymer present in the disk and on microorganism susceptibility.…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…Because the use of a single biopolymer has several shortcomings, combining two or more biopolymers to complement each other has emerged as a recent strategy. A few studies have demonstrated that films composed of composite biopolymers possess superior overall performance when compared to the films made of pure biopolymers (El‐Wakil, Kassem, & Hassan, ; Leuangsukrerk, Phupoksakul, Tananuwong, Borompichaichartkul, & Janjarasskul, ; Şengül, Demirci, & Caykara, ). For instance, the increase of polyethyleneimine (PEI) in the HPC–PEI films increase the elasticity and elongation at break (Şengül et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…A few studies have demonstrated that films composed of composite biopolymers possess superior overall performance when compared to the films made of pure biopolymers (El‐Wakil, Kassem, & Hassan, ; Leuangsukrerk, Phupoksakul, Tananuwong, Borompichaichartkul, & Janjarasskul, ; Şengül, Demirci, & Caykara, ). For instance, the increase of polyethyleneimine (PEI) in the HPC–PEI films increase the elasticity and elongation at break (Şengül et al., ). The KGM‐Whey protein isolate (WPI) blend films show preferable flexibility and transparency than KGM‐based films, and better tensile strength (TS) and elastic modulus than WPI‐based films (Leuangsukrerk et al., ).…”
Section: Introductionmentioning
confidence: 99%